2020
DOI: 10.2147/dddt.s243383
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anisodamine Suppressed the Growth of Hepatocellular Carcinoma Cells, Induced Apoptosis and Regulated the Levels of Inflammatory Factors by Inhibiting NLRP3 Inflammasome Activation</p>

Abstract: Introduction: Hepatocellular carcinoma (HCC) is a primary liver cancer with a 5-year incidence of over 70%. Anisodamine (ANI), an alkaloid extracted from Anisodus, has a good therapeutic effect in septic shock and morphine addiction. Our study designed to investigate the anticancer effect of anisodamine (ANI) on HCC. Materials and Methods: HepG2 cells were subcutaneously injected into BALB/C nude mice and the tumor tissue was subcutaneously inoculated to construct the transplanted tumor. Mice were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Different inhibitory compounds such as luteoloside and anisodamine have been shown to have antitumoral activity in vitro and in vivo, including the suppression of cell proliferation and the impairment of cell migration and invasion [ 168 , 169 ]. Further investigations are needed to better understand the precise mechanisms underlying inflammasome activation and to design inflammasome-directed therapies for CLD and HCC.…”
Section: Targeting Cell Death and Tumor Microenvironmentmentioning
confidence: 99%
“…Different inhibitory compounds such as luteoloside and anisodamine have been shown to have antitumoral activity in vitro and in vivo, including the suppression of cell proliferation and the impairment of cell migration and invasion [ 168 , 169 ]. Further investigations are needed to better understand the precise mechanisms underlying inflammasome activation and to design inflammasome-directed therapies for CLD and HCC.…”
Section: Targeting Cell Death and Tumor Microenvironmentmentioning
confidence: 99%
“…Furthermore, berberine exerted anticancer activity via targeting variant pathways, such as NF-κB/COX-2, p38/JNK, AP-2/telomerase reverse transcriptase (hTERT), cytochrome-c/caspase, and HIF-1α/VEGF signaling in human gastric and NSCLC cell lines ( 259 , 260 ). The alkaloid anisodamine ( Figure 6 ) is another anticancer compound that inhibited the growth, invasion, and proliferation of HepG2 cells and suppressed the expression and activation of IFN-γ, IL-27, NLRP3, IL-4, and TNF-α ( 261 ). In a similar study, a steroidal alkaloid, cyclopamine ( Figure 6 ), induced apoptosis and suppressed the proliferation of HEL and TF1a cells via induction of PKC, COX-2 overexpression, PARP cleavage, and modulation of MAPK/Akt signaling ( 262 ).…”
Section: Phytochemicals Augment Chemotherapy and Immunotherapy Throug...mentioning
confidence: 99%
“…Wei et al. conducted an ex vivo study and found that the downregulation of the NLRP3 inflammasome was associated with the genesis and development of HCC [ 81 , 82 ]. Additionally, Wei et al.…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…(B) The pathway of different cancers. Cancer type Level of pyroptotic components Associated consequences References (A) Esophagus cancer NLRP3↑ cell death and Barrett's esophagus [ 61 ] Upregulated GSDME transit the apoptosis to pyroptotic-signaling pathways [ 60 ] Gastric cancer GSDMD↓ cancer cell proliferation [ 62 ] GSDMA↓ anti-oncogenic factor [ 70 , 71 ] GSDMB↑ control tumor infringement [ 49 ] GSDMC cancer suppressor gene [ 73 ] DFNA5/GSDME signaling pathway pyroptosis facilitates GC progression [ 62 ] Hepatocellular carcinoma Caspase-1 protein↓ Tumor proliferation [ 80 , 84 ] NLRP3↓ Increase HCC etiology and progression [ 81 , 82 ] AIM2↑ Promote pyroptosis and antitumor effects [ 85 , 87 ] Colorectal cancer Caspase-1↑ Promote epithelial cell proliferation and apoptosis [ 54 ] Lack of AIM2 Poor prognosis in CRC [ 89 ] NLRP1↓ Tumor progression [ 88 , 91 ] GSDMC↓ Tumor cell proliferation ...…”
Section: Introductionmentioning
confidence: 99%